1992
DOI: 10.1002/hipo.450020109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic alcohol consumption and withdrawal on the somatostatin‐immunoreactive neurons of the rat hippocampal dentate hilus

Abstract: Previous studies have demonstrated that the dentate granule and the CA3 pyramidal cells of the rat hippocampal formation are neuronal populations vulnerable to the toxic effects of ethanol. It also has been shown that the resulting alterations do not end after withdrawal from ethanol. As the neurons in the dentate hilus are heavily interconnected with the dentate granule cells, the authors decided to examine the fate of the hilar neurons after chronic alcohol consumption and withdrawal, inasmuch as the hilar s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…GABAergic interneurons are particularly vulnerable to a variety of insults, including excitotoxicity (Shetty et al, 2009; Shetty and Turner, 2001), ischemic events (Bering et al, 1997; Johansen, 1993), and traumatic brain injury (Lowenstein et al, 1992; Schiavone et al, 2017). Previous research has also demonstrated that interneurons in a variety of brain regions are susceptible to damage by both developmental and postnatal EtOH exposure (Andrade et al, 1992; Moore et al, 1998). Developmental exposure to EtOH reduces interneuron populations in cortical areas (Miller, 2006; Moore et al, 1998; Smiley et al, 2015), and in the cerebellum (Nirgudkar et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…GABAergic interneurons are particularly vulnerable to a variety of insults, including excitotoxicity (Shetty et al, 2009; Shetty and Turner, 2001), ischemic events (Bering et al, 1997; Johansen, 1993), and traumatic brain injury (Lowenstein et al, 1992; Schiavone et al, 2017). Previous research has also demonstrated that interneurons in a variety of brain regions are susceptible to damage by both developmental and postnatal EtOH exposure (Andrade et al, 1992; Moore et al, 1998). Developmental exposure to EtOH reduces interneuron populations in cortical areas (Miller, 2006; Moore et al, 1998; Smiley et al, 2015), and in the cerebellum (Nirgudkar et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Few studies to date, however, have examined the substrates involved following periods of extended abstinence (Valdez et al ., 2002; Adams et al ., 2010). It has been documented that abstinence from alcohol results in a number of functional neuronal alterations that may contribute to propensity to relapse, including enhanced corticostriatal synaptic plasticity (Xia et al ., 2006), altered hippocampal inhibitory mechanisms and synaptic structure (Faingold et al ., 2004), and modification to neurotransmitter and receptor expression and function (Andrade et al ., 1992; Vizi et al ., 2000; Chandler et al ., 2006). It is unknown how these alterations may contribute to the mechanisms involved in relapse.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that neurons of the hippocampal formation are highly susceptible to insults and can degenerate as a result of various injuries. Neurons of the dentate gyrus and subpopulations of hippocampal pyramidal cells are affected following, for example, Alzheimer's disease, alcoholism, ischemia, and epileptic seizures (Chan-Palay, 1987;Andrade et al, 1992;Matsuyama et al, 1993;Obenaus et al, 1993;Sloviter, 1987). Attempts to characterize these neurons neurochemically have shown that they contain a variety of putative neurotransmitters, such as glutamate, GABA, neuropeptide Y (NPY) or somatostatin (SS'I'; de Lanerolle and Spencer, 1991;Kohler et al, 1987).…”
mentioning
confidence: 99%
“…Attempts to characterize these neurons neurochemically have shown that they contain a variety of putative neurotransmitters, such as glutamate, GABA, neuropeptide Y (NPY) or somatostatin (SS'I'; de Lanerolle and Spencer, 1991;Kohler et al, 1987). Of these hippocampal neurons, those containing SST have been found to degenerate the earliest and most consistently following insults (Andrade et al, 1992;Chan-Palay, 1987;Matsuyama et al, 1993) including epileptic seizures (Robbins et al, 1991;Sloviter, 1987). The reasons for the early degeneration of SST neurons are not known and could be due to direct or indirect effects of each pathogenesis on the ability of these neurons to function.…”
mentioning
confidence: 99%